Productivity metrics and their integration into DevOps - Riihimäki, Rasmus (My University, 2024)
This thesis addresses the challenge of measuring productivity in a DevOps environment, focusing on identifying effective metrics, understanding their impact on software quality, and assessing their influence on developer well-being. Productivity and its various definitions are analyzed from historical, modern, and practical perspectives. The modern and practical findings lead the thesis into the realm of DORA metrics and the annual DevOps report. The thesis was started with the goal of improving the current productivity measuring inside the case company. After conducting a literature review of the current research into productivity metrics, a case study where the current state of productivity metrics is assessed and improved within the DevOps teams at the case company is conducted. The methodology of this case study involves planning, executing, and validating the implementation of a productivity metrics dashboard. This approach sets an example for other organizations aiming to measure and enhance productivity using similar metrics. The findings from the case study at the case company indicate that adopting a modern productivity metrics approach enhances software quality. This is achieved by promoting a fast deployment process and agile DevOps practices. The data collected and analyzed show a positive correlation between the use of DORA metrics and improvements in both software quality and developer well-being. The case study suggests that implementing DORA metrics not only improves software quality but also supports developer well-being and self-reported productivity. By following the example set in this thesis, other organizations can plan, execute, and validate their productivity measurement processes, leading to enhanced software quality and a healthier, more productive development team.
Keywords: devops, productivity, dora, developer experience, metrics, software, self-reported productivity, software quality